Ambipolar 2D Semiconductors and Emerging Device Applications. Issue 1 (17th November 2020) - Hu, Wennan; Sheng, Zhe; Hou, Xiang; Chen, Huawei; Zhang, Zengxing; Zhang, David Wei; Zhou, Peng
Abstract: With the rise of 2D materials, new physics and new processing techniques have emerged, triggering possibilities for the innovation of electronic and optoelectronic devices. Among them, ambipolar 2D semiconductors are of excellent gate‐controlled capability and distinctive physical characteristic that the major charge carriers can be dynamically, reversibly and rapidly tuned between holes and electrons by electrostatic field. Based on such properties, novel devices, like ambipolar field‐effect transistors, light‐emitting transistors, electrostatic‐field‐charging PN diodes, are developed and show great advantages in logic and reconfigurable circuits, integrated optoelectronic circuits, and artificial neural network image sensors, enriching the functions of conventional devices and bringing breakthroughs to build new architectures. This review first focuses on the basic knowledge including fundamental principle of ambipolar semiconductors, basic material preparation techniques, and how to obtain the ambipolar behavior through electrical contact engineering. Then, the current ambipolar 2D semiconductors and their preparation approaches and main properties are summarized. Finally, the emerging new device structures are overviewed in detail, along with their novel electronic and optoelectronic applications. It is expected to shed light on the future development of ambipolar 2D semiconductors, exploring more new devices with novel functions and promoting the applications of 2D materials. Abstract : The unique properties of ambipolar 2D semiconductors enable possible breakthroughs in electronic and optoelectronic device applications. Recent progress in this field is briefly summarized, from fundamental principles, preparation methods, electrical contact engineering techniques, materials, and main performances to electronic and optoelectronic device applications like novel PN junctions and complementary metal oxide semiconductor‐like circuits.